PENGARUH TINGKAT PENDIDIKAN, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PRAMANA WATU KURUNG RESORT UBUD - Putu Ratna Juwita Sari; Ni Putu Diah Ratnawati (JURNAL ILMIAH EDUNOMIKA, 2024)
The level of education possessed by employees would be increased or decreased the work performance. Other factors that have influenced employee performance apart from educational background are the competencies obtained by employees and also the discipline that is very necessary in tourism. This research aims to investigated the effects of education level, competency, and work discipline on employee performance at Pramana Watu Kurung Resort Ubud. Specifically, the research will concentrate on identifying the effects of education level, competency, and work discipline. worker. The population consisted of 50 sampling, representing the entire workforce at Pramana Watu Kurung. The validity and reliability tests used on this research are multiple linear regression analysis, classical assumptions, F and t tests, and the coefficient of determination test are among the analyses employed in this study. The study's findings demonstrate that Pramana Watu Kurung employees perform better when they have a higher degree of education, competency, and work discipline all at once. At Pramana Watu Kurung Resort, employee performance is significantly positively impacted by education level. The Pramana Watu Kurung Resort finds that employee performance is significantly improved by competence. At Pramana Watu Kurung Resort, work discipline also significantly improves employee performance.